IN MEMORIAM: Francisco Javier Sánchez Escribano (1948-2014) - García Landa, Jose Ángel (Miscelánea: A Journal of English and American Studies, 2014)
IN MEMORIAM: Francisco Javier Sánchez Escribano (1948-2014)